Crystal growth of ZnO bar using joule heating - Har, Lai Yee (2016)
Crystal growth is important for understanding physiochemical mechanisms for zinc oxide (ZnO). ZnO exists in different crystal structures under specific condition and each of the crystal growth consists of different characteristics. The major problem for growing the ZnO crystal was to conduct electricity through the wide band gap semiconductor. As a solution, joule heating method was adopted to conduct electricity in this research. Joule heating method provided a stable and continuous current and high applied voltage throughout the circuit. New form of zinc oxide crystals was wished to be observed through this research. The three main objectives of this research were to grow various forms of ZnO crystals, master in conducting joule heating technique and characterize the samples through topography characterization, absorbance characterization, emission spectrum characterization and X-Ray Diffraction characterization. Scanning Electron Microscopy (SEM), Ultraviolet-Visible (UV-Vis) Spectroscopy, Photoluminescence Spectroscopy and X-Ray Diffractometer (XRD) were used for the characterization respectively. SEM showed the most of the crystals grew by each sample in the rock like shape and hexagonal shape. UV-Vis showed the wavelength of all samples was located around 380 nm. Therefore, the calculated exitonic energy was around 3.20 eV which was nearly matched with theoretical band gap 3.37 eV. The XRD results showed most of the crystals grew on the plane (1 0 1). The crystals grew were in rock like shape. This was proved by the plane (1 0 1) had the highest intensity in all the samples. As a conclusion, the optimum current for crystals grew was 3.0 A and the crystals were mostly grew in the plane (1 0 1). The easiest grew crystals were in rock and hexagonal shape.